Optimizing health services for young children in poverty: enhanced collaboration between Early Head Start and pediatric health care - Horm, Diane M.; Brophy-Herb, Holly E.; Peterson, Carla A. (Frontiers in Public Health, 2024)
Given the importance of health to educational outcomes, and education to concurrent and future health, cross-systems approaches, such as the Whole School, Whole Community, Whole Child (WSCC) framework, seek to enhance services typically in K-12 settings. A major gap exists in cross-systems links with early care and education serving children birth to age 5. Both pediatric health systems and early family and child support programs, such as Early Head Start (EHS) and Head Start (HS), seek to promote and optimize the health and wellbeing of infants, toddlers, preschoolers, and their families. Despite shared goals, both EHS/HS and pediatric health providers often experience challenges in reaching and serving the children most in need, and in addressing existing disparities and inequities in services. This paper focuses on infant/toddler services because high-quality services in the earliest years yield large and lasting developmental impacts. Stronger partnerships among pedicatric health systems and EHS programs serving infants and toddlers could better facilitate the health and wellbeing of young children and enhance family strengths and resilience through increased, more intentional collaboration. Specific strategies recommended include strengthening training and professional development across service platforms to increase shared knowledge and terminology, increasing access to screening and services, strengthening infrastructure and shared information, enhancing integration of services, acknowledging and disrupting racism, and accessing available funding and resources. Recommendations, including research-based examples, are offered to prompt innovations best fitting community needs and resources.